Estudo das intervenções diárias do Banco Central do Brasil sobre o mercado de câmbio nacional, sua volatilidade e conseqüência na procura por proteção - Geraldi, Ricardo Puccinelli (2008)
Central Bank of Brazil has been acting frequently in the Brazilian spot market with interventions in the past years. These interventions increase international reserves, but may also, among other consequences, act on the currency appreciation rhythm, as well as on the market volatility. The goal of this study was to identify if these interventions truly affected market volatility, concluding that there was a volatility reduction in only one band within the intervention universe of Central Bank’s spot transactions. Secondly, the goal was to identify what was the demand of market players for hedge instruments in response of such volatility reduction. It was not identified any effect over such demand. This analysis was based on the period between January, 2001 and May, 2007. The evaluation of the effects of interventions over the spot market was based on the GARCH model, and the subsequent evaluation, of the effect of these interventions over the market players, was based on the SARIMA model.